Posted by Ryan on September 13, 2002 at 15:28:24:
In Reply to: Re: Sinh - sin -Sinh - sin posted by Soroban on September 13, 2002 at 13:42:59:
: : Can anyone offer me a proof that...
: : i=sqrt(-1)
: : sin(ix) = isinh(x)
: Since you are working sinh(x), I assume you know
: the infinite series
: for sin(x) and sinh(x). [If I'm wrong - sorry!]
: Substitute ix into the sine series:
: sin(ix) = (ix) - (ix)^3/3! + (ix)^5/5! - (ix)^7/7! + ...
: = i[x + x^3/3! + x^5/5! + x^7/7! + ...]
: = i sinh(x)
Post a Followup